Juridical Analysis Of The Implementation Of Restorative Justice In The Settlement Of Fraud Cases At The Cirebon District Court - Nabiel Purwa Handiki; Ismayana Ismayana (Ann Publisher, 2026)
Background. This study examines the implementation of restorative justice in the settlement of fraud crimes at the Cirebon District Court and its conformity with the Criminal Code and the New Criminal Code. The research problem focuses on how the mechanism is applied and the factors that encourage its use. Aims. The purpose and objectives of this study are to conduct a juridical analysis of the implementation mechanism, identify supporting factors, and assess the effectiveness and harmony of restorative justice practices in realizing restoration-oriented justice. This research method uses normative and empirical legal approaches. Methods. Normative to analyze legal regulations and theories, while empirical to examine practices in the Cirebon District Court through interviews, observations, and document studies. The analysis was carried out in a descriptive-analytical manner. Result. The findings of the study show that restorative justice has been achieved substantially through the return of losses, peace, and the restoration of social relations. However, its application remains partial, as it continues to lead to criminal convictions. RJ is only a consideration of the judge, reflecting the transition from a retributive to restorative paradigm that is not optimal. Conclusion. This study shows that the application of restorative justice in the fraud case at the Cirebon District Court has been substantially carried out through the recovery of losses and the achievement of peace. However, its application remains limited because it is used only as a consideration in criminal prosecutions. Implementation. Although it has been in accordance with legal and theoretical provisions, its implementation has not been optimal due to the still-dominant retributive paradigm.